Control of interfacial properties in power electronic devices. (10th December 2012) - Maeda, Masakatsu; Takahashi, Yasuo
The present paper describes processes to control structures and properties of two interfaces in the next–generation power electronic devices. The first is the interface between semiconductors and contact electrodes. Processes to synthesise Ohmic conducting interfaces for p–type SiC and n–type GaN developed by the authors are shown. Ti3 SiC2 contact layer is formed on SiC by controlled interfacial reaction between SiC and Ti/Al bilayer using a stepwise heating scheme. On the other hand, it is shown that formation of Ti(C, N) contact layer on GaN can be enhanced by using TiC as a precursor for the interfacial reaction between GaN and Ti. The other interface is that between electrodes and wires. Heat resistant, ductile and highly electric conductive interfaces between Cu ribbons and Sn–coated Cu pads are formed by ultrasonic bonding.